The Ethiopian Jewish Exodus: Narratives of the Journey - BenEzer, Gadi (Routledge Studies in Memory and Narrative, 2002)
Between 1977 and 1985, some 20,000 Ethiopian Jews left their homes in Ethiopia and - motivated by an ancient dream of returning to the land of their ancestors, 'Yerussalem' - embarked on a secret and highly traumatic exodus to Israel. Due to various political circumstances they had to leave their homes in haste, go a long way on foot through unknown country, and stay for a period of one or two years in refugee camps, until they were brought to Israel. The difficult conditions of the journey included racial tensions, attacks by bandits, night travel over mountains, incarceration, illness and death. A fifth of the group did not survive the journey. This interdisciplinary, ground-breaking book focuses on the experience of this journey, its meaning for the people who made it, and its relation to the initial encounter with Israeli society. The author argues that powerful processes occur on such journeys that affect the individual and community in life-changing ways, including their initial encounter with and adaptation to their new society. Analysing the psychosocial impact of the journey, he examines the relations between coping and meaning, trauma and culture, and discusses personal development and growth. Gadi BenEzer is a senior lecturer of psychology and anthropology at the Department of Behavioural Sciences in the College of Management in Tel Aviv. In the last two decades he has worked as a psychotherapist and organizational psychologist with the Ethiopian Jewish immigrants in Israel. He has written extensively on Ethiopian Jews, trauma and life stories, and cross-cultural psychotherapy. His book on Immigration and Integration of the Ethiopian Jews has become the main text on the subject in Israel. "Thousands of Ethiopian (Beta Israel) Jews arrived in Israel following a perilous journey on foot from their original villages in Gondar to refugee camps in Sudan. This difficult and lengthy journey and waiting period forms the subject of this excellent book... While geared to specialists, this book may be read with profit by anyone interested in the phenomenon of immigration and in the Beta Israel experience. Highly recommended." - Choice